Transarterial chemoembolization plus apatinib with or without camrelizumab for unresected hepatocellular carcinoma: A two-center propensity score matching study - Zhu, Di; Ma, Kun; Yang, Wei; Zhou, Hai-Feng; Shi, Qi; Ren, Jian-Wu; Xie, Yu-Guan; Liu, Sheng; Shi, Hai-Bin; Zhou, Wei-Zhong (Frontiers in Oncology, 2022)
Purpose: To compare the effectiveness and safety of transarterial chemoembolization (TACE) combined with apatinib and camrelizumab with those of TACE as well as apatinib among patients with unresectable hepatocellular carcinoma (HCC). Materials and Methods: The data of patients with unresectable HCC (uHCC) who received TACE-apatinib-camrelizumab combination (TACE + AC group) and TACE-apatinib combination (TACE + A group) were collected from two centers between January 2018 and January 2022. Propensity score matching (PSM) was conducted to diminish the bias between the two groups. The primary outcome measures of the study were overall survival (OS) and progression-free survival (PFS), and the secondary outcome measures were response rate (ORR), disease control rate (DCR), and adverse events (AEs). Results: A total of 102 patients were enrolled in this study after PSM, with 34 patients in the TACE + AC group and 68 patients in the TACE + A group. Compared to the TACE + A group, TACE + AC had a significantly longer OS (25.5 months, interquartile range [IQR], 23.5–33.0) than 18.5 months (IQR, 13.0–25.0; P = 0.001). Similarly, the PFS of the TACE + AC group was significantly improved (14.0 months, IQR, 9.0–NA) compared to that of the TACE + A group (5.0 months, IQR, 2.5–9.0; P = 0.001). The ORR rates (55.9% vs. 51.5%), and DCR rates (79.4% vs. 72.1%) were comparable between groups (P > 0.05). All treatment-related adverse events were tolerable and manageable, and no serious adverse events were observed. Conclusion: TACE combined with apatinib plus camrelizumab demonstrated superior efficacy to TACE plus apatinib for patients with unresectable HCC. The two combination therapies showed similar safety profiles.